2008
DOI: 10.1007/s10584-008-9412-2
|View full text |Cite
|
Sign up to set email alerts
|

Land cover change and soil organic carbon stocks in the Republic of Ireland 1851–2000

Abstract: Using both historic records and CORINE land cover maps, we assessed the impact of land cover change on the stock of soil organic carbon (SOC) in the Republic of Ireland from 1851 to 2000. We identified ten principal land cover classes: arable land, forest, grassland, heterogeneous agricultural areas/other, nonvegetated semi-natural areas, peatland, suburban, urban, water bodies, and wetland. For each land cover class, the SOC stock was estimated as the product of SOC density and land cover area. These were sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 33 publications
1
59
2
5
Order By: Relevance
“…Grassland was split into the sub-classes Improved (GA) and SemiImproved (GS) in recognition of the ecological and economic importance of pasture in Ireland, where this particular land-cover type accounts for 55% of the total land surface and 90% of the agricultural areas (Eaton, 2008). Cropland was omitted due to its small parcel sizes and scarcity in the study area.…”
Section: Land Cover Classes and Ground Truthmentioning
confidence: 99%
“…Grassland was split into the sub-classes Improved (GA) and SemiImproved (GS) in recognition of the ecological and economic importance of pasture in Ireland, where this particular land-cover type accounts for 55% of the total land surface and 90% of the agricultural areas (Eaton, 2008). Cropland was omitted due to its small parcel sizes and scarcity in the study area.…”
Section: Land Cover Classes and Ground Truthmentioning
confidence: 99%
“…Land use change (LUC) is considered the second greatest cause of C emissions after fuel consumption (Watson et al, 2000). LUC has contributed to soil degradation and soil loss, leading to a decrease in soil C storage worldwide (Eaton et al, 2008), and even more intensely in the Mediterranean areas during the last few decades (Cerdà et al, 2010). Longterm experimental studies have confirmed that SOC is highly sensitive to LUC (Smith, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…P R E -P R I N T V E R S I O N disponibilidad de nutrientes para las plantas (Brevick, 2009;Ruiz-Sinoga et al, 2012;Tesfahunegn, 2013). La materia orgánica de los suelos es el producto de la descomposición química de las excreciones de animales y microorganismos, de residuos de plantas o de la degradación de cualquiera de ellos tras su muerte (Eaton et al, 2008;Parras-Alcántara et al, 2013). En este sentido, numerosos estudios han descrito cómo el uso de enmiendas orgánicas podría constituir una manera eficaz de incrementar el SOC y así, a largo plazo, favorecer la estructura y actividad microbiológica de ambientes degradados (Albiach et al, 2001;Roldán et al, 2001;Ferreras et al, 2006).…”
Section: Cambios Estructuralesunclassified
“…Los suelos constituyen un recurso básico por lo que su "salud" debe de ser conservada en aras de mantener la productividad y diversidad de los ecosistemas terrestres (COM, 2002;Eaton et al, 2008). Así, juegan un papel fundamental en la provisión de alimentos, ayudan a mantener la calidad de aire y agua y son grandes proveedores de biodiversidad (Keesstra et al, 2016).…”
Section: Introductionunclassified